"Everyone Needs a Breath of Fresh Air": Workplace Impact on Nurses' Smoking Behaviors - Petersen, Anne Berit; Sarna, Linda; Rezk-Hanna, Mary; Wells, Marjorie; Nohavova, Iveta; Bialous, Stella (Cancer nursing, 2020)
BACKGROUND: Europe continues to have among the highest worldwide prevalence of adult smoking (28%) and the highest among females (19%). Nurses' rates of smoking in the region are comparable or higher than the general female population. Nurses who smoke are less likely to intervene with patients who smoke; therefore, supporting nurses' efforts to quit is critical to promoting nurses' well-being and strengthening the profession's impact on prevention of tobacco-induced diseases. OBJECTIVE: The aim of this study was to explore nurses' perceptions of hospital workplace factors that influence nurses' smoking and quitting behaviors in Central and Eastern Europe. METHODS: Each country had a project director involved in the recruitment of participants and the translation of instruments. Using a moderator guide, focus groups (N = 9) about smoking and quitting were conducted in 5 countries (Czech Republic, Hungary, Romania, Slovakia, Slovenia) among 82 nurses who self-reported as current or former smokers. Recorded transcripts were translated and analyzed using content analysis methods. RESULTS: The majority of nurses were female (94%) and currently smoking (65%). Four major themes were identified that describe workplace factors influencing nurses' smoking behaviors and efforts to quit: (1) taking breaks, (2) effect of smoking on patient interactions, (3) perceived collegial support for quitting, and (4) impact of workplace policies. CONCLUSIONS: Workplace factors influence nurses smoking and quitting behaviors. IMPLICATIONS FOR PRACTICE: Changes in healthcare systems and policies are needed to support nurses' quit efforts. Additional education is needed to ensure that nurses understand issues related to smoking and interactions with patients.
Keywords: personál sesterský nemocniční; kouření; Workplace; Europe; Attitude of Health Personnel; Evropa; Middle Aged; mužské pohlaví; Adult; postoj zdravotnického personálu; Focus Groups; Smoking Cessation; Smoking; ženské pohlaví; Humans; zjišťování skupinových postojů; pracoviště; lidé středního věku; Nursing Staff, Hospital; dospělí; Female; odvykání kouření; lidé; Male